2021
DOI: 10.1111/ijac.13744
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and ion exchange of zeolites produced from kaolin for separation of oxygen from atmospheric air

Abstract: Lithium‐based zeolites are the most commonly used materials in PSA (pressure swing adsorption) oxygen concentration from atmospheric air. Synthesizing these adsorbents using mineral raw materials adapts to worldwide environmental requests, as only high‐purity chemical reactants such as aluminates and silicates are usually used. The present work aims to synthesize and characterize zeolites using kaolin as raw material by studying the influence of the metakaolinization temperature and SiO2/Al2O3 and H2O/Na2O mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…From the DTG curve, it is clearly observed that the conversion of kaolin into metakaolin starts from 500 °C. From the DTA curve, it is observed that the endothermic region corresponds to the water loss and the exothermic region corresponds to material stability and phase change of the materials. ,, The obtained results of thermal studies are found to be in good agreement with the XRD results, and it clearly indicates that the zeolite synthesized at higher temperatures above 800 °C has more of an impurity phase when compared with zeolite synthesized at lower temperatures.…”
Section: Resultssupporting
confidence: 58%
“…From the DTG curve, it is clearly observed that the conversion of kaolin into metakaolin starts from 500 °C. From the DTA curve, it is observed that the endothermic region corresponds to the water loss and the exothermic region corresponds to material stability and phase change of the materials. ,, The obtained results of thermal studies are found to be in good agreement with the XRD results, and it clearly indicates that the zeolite synthesized at higher temperatures above 800 °C has more of an impurity phase when compared with zeolite synthesized at lower temperatures.…”
Section: Resultssupporting
confidence: 58%
“…132,[156][157][158] We can assume that if there are Al IV atoms in the raw material, less energy is expended to convert the residual Al V and Al VI into Al IV during hydrothermal synthesis, and it accelerates the formation of zeolite. The silicon atoms are tetrahedral at all the above steps, and there is only one peak on the 29 Si MAS NMR spectra. 159 Fig.…”
Section: Dion Et Al Based On Simulations Of Metakaolinisation Under I...mentioning
confidence: 99%
“…Feltrin et al have synthesised zeolite X in a mixture with zeolites P and A using metakaolin obtained at 800 and 900 °C for 2 h. 29 Other things being equal, the metakaolin obtained at 900 °C always gave less zeolite A with Si/Al = 1 and more zeolites X and P with Si/Al > 1. It can be attributed to the decrease of active Al 2 O 3 (or Al IV ) and the increase of active SiO 2 in metakaolin obtained at 900 °C compared to metakaolin obtained at 800 °C.…”
Section: Dion Et Al Based On Simulations Of Metakaolinisation Under I...mentioning
confidence: 99%
See 1 more Smart Citation